Resistance training for the elderly. Review of the literature - Anna Traczyk; Karolina Kuźba; Joanna Chłystek; Kamil Potyra; Agata Abramczyk; Mateusz Łakomski (Kazimierz Wielki University, 2018)
With age, there is a gradual decrease in muscle mass and strength, and the use of strength training contributes to the slowdown of this process. It is also recommended in older people due to the increase in bone mass. An important element of planning this type of training, including the advancement of the person exercising is their lifestyle and the results obtained in strength tests. Due to the age, remember to exercise caution when doing this type of exercise and monitor the course of the training, e.g. by controlling the exercising heart rate or using the Borg scale. Avoid extreme strength and endurance exhaustion as it results in an increase in blood pressure. Strength training brings a number of benefits, but unpredictably planned and conducted also a number of threats. It is indicated in some disease entities, e.g. obesity.